The Effect of Physical Quality Improvement to Inhabitant’s Sense of Place (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Sense of place is closely related to the level of community participation and sustainability development. In this paper, the context of environment is tourism kampung. Tourism kampung has a dynamic activities and cultural values both tangible and intangible. The development of tourism kampung has a positive goal to improve inhabitant’s socio-economic welfare. But, there was a change in kampung’s function, activity and meaning from a closed settlement system with low social accessibility to a tourism kampung. This change can also affect the people’s sense of place. Research method used in this study is mixed method, which combines quantitative and qualitative research. Data collection techniques were obtained from questionnaires, field observations, and in depth interviews. The result shows that physical improvement has a positive effect in escalating the level of inhabitant’s sense of place. The finding will be important to the development of the sense of place’s theory and sustainable development.